Incidence of nonresponse and individual patterns of response following sprint interval training - Gurd, B. J.; Giles, M. D.; Bonafiglia, J. T.; Raleigh, J. P.; Boyd, J. C.; Ma, J. K.; Zelt, J. G. E.; Scribbans, T. D. (Applied Physiology, Nutrition, and Metabolism, 2016)
The current study sought to explore the incidence of nonresponders for maximal or submaximal performance following a variety of sprint interval training (SIT) protocols. Data from 63 young adults from 5 previously published studies were utilized in the current analysis. Nonresponders were identified using 2 times the typical error (TE) of measurement for peak oxygen uptake (2 × TE = 1.74 mL/(kg·min)), lactate threshold (2 × TE = 15.7 W), or 500 kcal time-to-completion (TTC; 2 × TE = 306 s) trial. TE was determined on separate groups of participants by calculating the test-retest variance for each outcome. The overall rate of nonresponders for peak oxygen uptake across all participants studied was 22% (14/63) with 4 adverse responders observed. No nonresponders for peak oxygen uptake were observed in studies where participants trained 4 times per week (n = 18), while higher rates were observed in most studies requiring training 3 times per week (30%-50%; n = 45). A nonresponse rate of 44% (8/18) and 50% (11/22) was observed for the TTC test and lactate threshold, respectively. No significant correlations were observed between the changes in peak oxygen uptake and TTC (r = 0.014; p = 0.96) or lactate threshold (r = 0.17; p = 0.44). The current analysis demonstrates a significant incidence of nonresponders for peak oxygen uptake and heterogeneity in the individual patterns of response following SIT. Additionally, these data support the importance of training dose and suggest that the incidence of nonresponse may be mitigated by utilizing the optimal dose of SIT.